Heterosis in bottle gourd (Lagenaria siceraria) over two varied seasons - Singh, PP; Singh, SP; Pandey, Sudhakar (Vegetable Science, 2011)
Combining ability and heterosis studies carried out through line x tester method using 10 lines and 3 testers. The expression of significant and desirable heterobeltiosis and standard heterosis in general and specific combining ability effect was examined. The 9 and 3 crosses exhibited positive and significant heterobltiosis and standard heterosis marketable yield per plant, respectively. The crosses had positive, negative and average sca effect for this character in almost same frequencies. Similar trends were also observed for most of the other characters, which suggested that there was a no apparent relationship between manifestations of heterosis with sca effect. However majority of crosses showing positive and significant heterobeltiosis and standard heterosis for marketable yield per plant in the two environments involved high x high general combiner parent followed by high x low and high x medium combination. This suggested existence of some correlation between heterosis of crosses, gca effect of their parents in which the involvement of at least one good general combiner parent appears very important for expression of high heterotic responses not only for marketable yield per plant, but also most of the other characters under study.